Assessment of genetic differentiation among relict populations of calophyllum brasiliense camb. (calophyllaceae) from northeast Argentina - Percuoco, Cecilia Beatriz (2014)
Calophyllum brasiliense is a tropical tree that grows exclusively in riparian forest and in almost permanently flooded areas. In Argentina two small populations located within riparian forest from Misiones and Corrientes Provinces have been recently identified. These riparian communities have been extensively fragmented and are at risk of local extinction due to flooding caused by a nearby dam and other anthropogenic changes that threaten this habitat. Genetic characterization using information from 56 RAPD loci revealed low expected heterozygosity in both populations (He = 0.273). Most genetic variability was distributed within populations, and a significant ϕST statistic value (0.283, p<0.05) showed the existence of a large genetic differentiation between them. Furthermore, the SGS analysis revealed a nonrandom distribution of genotypes in Misiones? population. Although these populations could have belonged to a large and continuous forest in the past, the process of habitat fragmentation may have favoured the divergence between them; sufficient time has passed to cause their genetic differentiation. As these populations represent the new southernmost species distribution, the genetic information obtained in this study should be analyzed in conjunction with ecological evaluations in order to develop management strategies that can ensure its conservation.